2022
DOI: 10.1021/acsnano.2c06032
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Direct Patterning of High-Resolution Full-Color Quantum Dot Arrays by Programmed Microwetting

Abstract: Although the commercialization of electroluminescent quantum-dot (QD) displays essentially demands multicolor patterning of QDs with sufficient scalability and uniformity, the implementation of QD patterning in a light-emitting diode device is highly challenging, mainly due to the innate vulnerability of QDs and charge-transport layers. Here, we introduce a noninvasive surface-wetting approach for patterning full-color QD arrays on a photoprogrammed hole-transport layer (HTL). To achieve noninvasiveness of QD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As shown in Figure 3e,f, the CdSe QLEDs show good device performances with high EQE reaching 15.6% and large brightness S2, Supporting Information). [17,18,24,29,30,[42][43][44][45][46] The patterned CdSe QLED device performance is comparable with the un-patterned ones of 15.3% (Figure S7, Supporting Information), suggesting no damage of the QD electroluminescent property after patterning the QDs with our proposed QD pixel deposition strategy of EF-ID. Meanwhile, the device performances with different PEI thicknesses were also studied (Figure S8, Supporting Information), in which the QLED with 20 nm PEI showed the highest EQE and luminance, and the performance began to decline at a larger thickness owing to the deteriorated quality of QD patterns induced by the decreased zeta potential (Figure 2f).…”
Section: Resultsmentioning
confidence: 64%
“…As shown in Figure 3e,f, the CdSe QLEDs show good device performances with high EQE reaching 15.6% and large brightness S2, Supporting Information). [17,18,24,29,30,[42][43][44][45][46] The patterned CdSe QLED device performance is comparable with the un-patterned ones of 15.3% (Figure S7, Supporting Information), suggesting no damage of the QD electroluminescent property after patterning the QDs with our proposed QD pixel deposition strategy of EF-ID. Meanwhile, the device performances with different PEI thicknesses were also studied (Figure S8, Supporting Information), in which the QLED with 20 nm PEI showed the highest EQE and luminance, and the performance began to decline at a larger thickness owing to the deteriorated quality of QD patterns induced by the decreased zeta potential (Figure 2f).…”
Section: Resultsmentioning
confidence: 64%
“…Aria [ 57 ] reported that adding active oligomeric surfactants to the solution results in more uniform diffusion of impacting droplets. Splashing during printing is suppressed, and diffusion is very uniform; this approach thus holds great potential for high-resolution printing requirements, as shown in Figure 3 c. Song [ 58 ] introduced a method to pattern quantum dot arrays by controlling the evaporation and diffusion of microdroplets on the substrate; this method was used for preparing high-resolution full-color quantum dot arrays, thus achieving non-invasive direct patterning of quantum dots, as shown in Figure 3 d. Zhu [ 47 ] used a mixture of mineral oil and red dye as ink and achieved efficient printing by adjusting flow rate and ink concentration, as shown in Figure 3 e. Rivers [ 52 ] developed a method for preparing stable large-area droplet-demand conductive polymer inks for 3D printing of electronic products, using a bio-renewable co-solvent to address the poor stability and large-area droplet-demand issues associated with conductive polymer inks, as shown in Figure 3 f.…”
Section: Liquid Modification For Printing Materialsmentioning
confidence: 99%
“…( d ) Diagram of the principles of non-invasive programmed-patterning (NIPP). Reproduced with permission from [ 58 ], published by the American Chemical Society, 2022. ( e ) Trajectory of ink droplets in the separation phase.…”
Section: Figurementioning
confidence: 99%
“…To overcome these challenges, Song et al developed a QD patterning process based on the selective-wetting principle, and demonstrated full-color QLEDs. 39 They adopted deep ultra-violet (UV) induced photo-programming to modify the surface of HTLs. The control of the UV irradiation time minimized the damage to the HTLs while maintaining the surface energy selectivity.…”
Section: Qd Patterning Technologiesmentioning
confidence: 99%